Elements of international economics - Gandolfo, Giancarlo (Berlin : Springer, 2004)
This book explores the determinants of international flows of commodities and financial assets as well as examining the effects of these flows on the domestic and international economy and the possible policy actions at the national and international level.
Includes bibliographical references and index.
osa 23/07/13
Loans
Keywords: International economic relations; Foreign exchange market; International finance; International trade